Legal Protection of Workers' Rights in Indonesia - Abdullah Izza Aprilla; Ghariza Azzahra Baidlowi; Mahendra Jaya Gumilang; Nabilla Dea Azzhramajid; Muchamad Ilham Utomo Putro (Universitas Muhammadiyah Surakarta, 2022)
One of the backgrounds for the birth of Law Number 13 of 2003 concerning Manpower is that several laws and regulations that have been in force so far have placed workers in a disadvantageous position in the service of manpower placement and the industrial relations system that emphasizes differences in position and interests, so that it is seen as not in accordance with the needs of the present and the demands of the future. The enactment of Law Number 13 of 2003 concerning Manpower is expected to: Enforce the problem of protection and guarantees for workers; Implement various international instruments on labor rights that have been ratified; As a member of the United Nations (UN) uphold and implement the Universal Declaration of Human Rights (HAM). Legal protection has been regulated in: the Preamble to the 1945 Constitution, which is based on Pancasila; the 1945 Constitution, namely: Article 27 paragraph 2, Article 28 D paragraph 1, paragraph 2, Article 33; Law Number 13 of 2003 concerning Manpower, and other regulations. Legally, the position of workers is free and balanced, but in practice it often creates an unbalanced situation, causing problems. To overcome this, a solution is needed so that it can be well received by all parties, is felt to be useful, has legal certainty and provides protection for all parties. The discussions in this study are: 1. How is the implementation of legal protection for workers' rights in labor relations in Indonesia. 2. Obstacles and efforts that must be made in providing legal protection for workers' rights in labor relations in Indonesia. The method used is normative juridical. Legal protection is provided in accordance with Pancasila and the 1945 Constitution.